Sex Ratio Complexity in Selected States: A Tentative Observation - Abdul Matin AND Jaya (Journal of Exclusion Studies, 2016)
Sex ratio is one of the important indicators reflecting the status of girl child as well as women in Indian society. This paper makes an attempt in examining complex trends of sex ratio at the district level in selected states. State level data may not be considered truly representative as district level data reveals a paradoxical situation. A close examination of 2011 census data reveals that some districts are much below the State average; whereas, other districts show low sex ratio. These trends require explanation different from State level average. It has been argued that sex ratio variations at the district level or even below district level may provide us better insights than the conventional understanding of the State level averages. This may have implications for policy and planning in order to address the social problems of gender discrimination. In this background, we have comparatively analysed seven states of India viz. Haryana, Rajasthan, J&K, Uttar Pradesh, Nagaland, Tamil Nadu and Kerala, as states of north and west are notorious for discrimination against women, the manifestation of which is apparent through the sex ratio of respective states. And now this serious problem is also making its inroad into southern and eastern states too. This phenomenon is supported by advancement in reproductive technologies and their use for sex determination and elimination of unwanted female foetus, which is responsible for adversely increasing gender disparity as reflected through child sex ratio in India, which is negating the notion of woman empowerment rather contributing in declining the status of women and girl child. It has been shown in the paper that in best performing states there are worst performing district, which are comparable to states and districts with low sex ratio and vice-versa.